Effect of different biochar on acidic soil, growth, and nutritional status of oil palm (Elaeis guineensis Jacq.) under the nursery conditionrsery condition. - ALEIADEH, HEMAM (International Journal of Horticultural Science, 2025)
Biochar is a widely known organic amendment that enhances plant growth and productivity through improving soil condition and fertility. However, plant and soil response differently to various types of biochar. Therefore, the major objective of the present study was to determine the effect of two types of biochar; vetiver grass biochar (VGB) and pineapple leaf biochar (PLB) on selected soil properties and understand their role in improving plant growth and nutritional status. Net house experimental study with oil palm (Elaeis guineensis Jacq.) seedlings was conducted at the farm unit of UiTM Samarahan campus for 240 days between November 2022 and July 2023 in order to understand the impact of different application rates (25, 50, 75, and 100%) of vetiver grass biochar and pineapple leaf biochar on selected soil properties including pH, electrical conductivity (EC), nitrogen, phosphorus, and potassium content, plant growth parameters including plant height, bole diameter, leaf number, SPAD chlorophyll content, plant dry weight, and plant’s NPK content. The experimental design used is randomized complete block design (RCBD) with 8 treatments, 3 replicates, and each replicate has 6 plants. The analysis of variance (ANOVA) and DMRT were used to analyze the collected data from soil and plant parameters. The analysis process was accomplished using SAS package (P